PENINGKATAN KREATIVITAS ANAK MELALUI PEMANFAATAN BARANG BEKAS (Penelitian Tindakan di Kelompok B PAUD Bintang, Jakarta 2015) - Ine Nirmala; Feronica Eka Putri (Wahana Karya Ilmiah Pendidikan, 2017)
This research aims to describe the process and outcomes of learning to use waste material in improving creativity of the child. The research was carried out in PAUD Bintang, Jakarta start on Mei to June 2015. The subjects were group B student consisting of 11 student, 6 boys and 5 girls. This research using action research method with Kemmis and Mc.Taggart model consist of: a)planning, b)acting observing, c)reflecting. Conducted over 16 meetings that are divided into two cycles, techniques of data collection is done through tests, observation, interview and documentation study. Data analysis technique used in this research is the analysis of qualitative and quantitative data. Quantitative data analysis used to determine the percentage of children creativity increase after the action. Qualitative analysis is used to describe the results of research. The results showed an increase in children after learning followed by using waste material. A pre-action Research was conducted to determine the percentage of the initial result of children creativity, 31.6% as the average grade, increased to 51.3% after the first cycle, and increased to 80.4% after the second cycle. The process of learning using waste material give an impact on various aspects of child development such as; fine motor, visual spatial, language, And interpersonal skill. The implication of this research is the process of early childhood learning strategy use waste materials can be considered as a objects for the improvement of children's creativity. Key Words: creativity, waste material objects, action research